Inclusive Theory in Integrative Practice (Training and Practice : Journal of Educational Sciences, 2017)
The framework of integrated education at schools in Hungary has been operating since 1989. At first it was optional for schools, later it became more and more popular especially because of the Public Education Law of 2003 (LXI.) which stopped the “unjustified separation” of students. Integrated study groups represent a high level of student-heterogeneity to which teachers have to adjust in order to teach them. The goal of our research is to explore the effects of “inclusion” in pedagogical practice at present and how unified their view on this topic is. In order to reach this we analysed the opinion of 178 practising teachers about integration, methods applied in class, assessment of students and contact with specially trained professionals. According to our data, the different levels of participation in teaching integrated study groups is not necessarily followed by a different approach.